1990
DOI: 10.1177/0148607190014004362
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding in the Hypoalbuminemic Patient

Abstract: Previous studies have correlated intolerance of isotonic, intact protein enteral solutions with hypoalbuminemia. The purpose of this retrospective study was to determine whether the level of serum albumin (SA) influenced tolerance of such an enteral nutrient solution (ENS). All patients who received Entrition during 1987 for a minimum of 48 hr were studied for the first 10 days of enteral feeding. Documentation included SA, medications, stool frequency, gastric residuals (GR), and daily caloric intake. ENS int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The osmolarity of usual feeds is no longer regarded as a major cause of diarrhea [18]. These results were confirmed by some authors [20,21] but not by all [22]. Several other risk factors for diarrhea have been reported and may depend on the treatment or the severity of the patient's condition.…”
Section: Discussionmentioning
confidence: 73%
“…The osmolarity of usual feeds is no longer regarded as a major cause of diarrhea [18]. These results were confirmed by some authors [20,21] but not by all [22]. Several other risk factors for diarrhea have been reported and may depend on the treatment or the severity of the patient's condition.…”
Section: Discussionmentioning
confidence: 73%
“…Enquanto BRINSON e KOLTS (10) em estudo prospectivo não-controlado com 35 pacientes de UTI, verificaram que todos aqueles com diarréia apresentavam albumina sérica <2,5 g/dL, PATTERSON et al (36) não observaram esta associação. Embora na casuística presente a albumina sérica à admissão (2,1 g/dL) do grupo com diarréia tenha sido menor que aquela dos pacientes sem diarréia (2,4 g/dL) (Tabela 3), isto não se manteve na análise multivariada (Tabela 4).…”
Section: Discussionunclassified
“…Brinson and Kolts [34] suggested that hypoalbuminemia in ICU patients with multiple organ failure was one of the factors responsible for an increased incidence of diarrhea with enteral nutrition and that peptide-based formulas could improve enteral nutrition tolerance. Patterson et al [35] did not find a statistically significant difference in enteral nutrition tolerance and diarrhea incidence between patients with serum albumin < or > 25 g/l in a metabolic support unit. Mowatt-Larssen et al [36] found no significant difference in the incidence of diarrhea between critically ill patients fed oligomeric and polymeric formulas, nor was there a significant difference in the incidence of diarrhea in patients with serum albumin concentrations of <25 g/l.…”
Section: Endogenous Factors Affecting Tolerancementioning
confidence: 92%